2013
DOI: 10.1007/s11906-013-0378-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hypertension in Childhood

Abstract: There is growing concern about elevated blood pressure in children and adolescents, because of its association with the obesity epidemic. Moreover, cardiovascular function and blood pressure level are determined in childhood and track into adulthood. Primary hypertension in childhood is defined by persistent blood pressure values ≥ the 95th percentile and without a secondary cause. Preventable risk factors for elevated blood pressure in childhood are overweight, dietary habits, salt intake, sedentary lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 79 publications
0
49
0
7
Order By: Relevance
“…A meta-analysis of controlled trials on infants and children [ 13 ] showed that 54 % reduction in salt intake among infants (aged newborn to 3 months old) resulted in a signifi cant decrease in systolic blood pressure (−2.47 mmHg; p < 0.01), while 42 % salt intake reduction among children aged [8][9][10][11][12][13][14][15][16] years resulted in reduced systolic blood pressure (−1.17 mmHg, p < 0.001) and reduced diastolic blood pressure (−1.29 mmHg, p < 0.0001). It is now recognized that blood pressure in childhood tracks into adulthood, and although a positive sodium balance is needed for growth during the fi rst year of life, a low salt diet for older children and adolescents has been shown to have the same cardiovascular protective effects as for adults [ 14 -16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of controlled trials on infants and children [ 13 ] showed that 54 % reduction in salt intake among infants (aged newborn to 3 months old) resulted in a signifi cant decrease in systolic blood pressure (−2.47 mmHg; p < 0.01), while 42 % salt intake reduction among children aged [8][9][10][11][12][13][14][15][16] years resulted in reduced systolic blood pressure (−1.17 mmHg, p < 0.001) and reduced diastolic blood pressure (−1.29 mmHg, p < 0.0001). It is now recognized that blood pressure in childhood tracks into adulthood, and although a positive sodium balance is needed for growth during the fi rst year of life, a low salt diet for older children and adolescents has been shown to have the same cardiovascular protective effects as for adults [ 14 -16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these cardiovascular complications first appear in adulthood, indicating that is not possible to directly link BP levels in childhood with cardiovascular disease risk in adulthood. Nevertheless, a correlation between BP and surrogate markers of target-organ damage, such as left ventricular hypertrophy, arterial stiffness or increased urinary protein excretion, is demonstrable in children with arterial hypertension [3]. Severe hypertension in childhood mainly results from secondary causes, such as cardiac or renal disease.…”
Section: Short-term and Long-term Consequences Of Arterial Hypertensimentioning
confidence: 99%
“…The most significant long-term consequence of elevated BP in childhood is the ongoing hypertension into adulthood (tracking of BP [5]), therefore causing cardiovascular, cerebrovascular and renal disease later in life [3,5,6,21,22]. The most evident target-organ damage during childhood and adolescence is left ventricular hypertrophy [8,9].…”
Section: Short-term and Long-term Consequences Of Arterial Hypertensimentioning
confidence: 99%
See 2 more Smart Citations